Effectivity of Polyscias obtusa Simplicia as Immunomodulator on CaecaTonsil of Broiler Post Infection of Salmonella typhimurium - Farsely, Mutya; Djati, Muhammad Sasmito; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2013)
Antibiotics usually used to protect the animals from pathogens, but antibiotics have residues which have negative side efect. Antibiotics can substituted with Polyscias obtusa simplicia because this plant contains a chemical compound called Flavonoid which roles in immune system as immunomodulator. This study aimed to determine the mobilization and development of CD4+, CD8+ and B220+ T-Cells lymphocytes from thymus of broiler that have been given additional feed Polyscias obtusa after infected by Salmonella typhimurium and determine the optimum dose of the addition of simplicia's Polyscias obtusa which can influence the mobilization of T-Cells lymphocyte in Thymus. The procedure are confirmation of the Salmonella typhimurium isolates, prepare the simplicia's Polyscias obtusa and Salmonella typhimurium bacterial culture, orally infections in 500 µl, prepare supplemented feeds by three doses (i.e. dose 1 (0.08%), dose 2 (0.16%) and dose 3 (0.26%)), thymus and T-Cells lymphocytes isolation and Flowcytometry analysis. The results showed that feeding with antibiotical feed + Salmonella infection and natural feed with additional Polyscias obtusa simplicia's dose 2 (0.16%) have increased the relative number of CD4+, CD8+ and B220+. T-Cells lymphocytes of thymus with different time feeding period have significant differences for relative number of CD8+. This result gave proof that Polyscias obtusa simplicia have the ability and influence to increase the body's immune system. Keywords : Broiler, Polyscias obtusa, Salmonella typhimurium, T-Cells lymphocyte, Thymus